EDUCATIONAL IDEAL CURRICULUM ISLAM AS AN EDUCATIONAL BLUEPRINT (HOPE, CHALLENGE, AND UPDATE) - Afif Syaiful Mahmudin (IAIN PONOROGO, 2022)
Kurikulum pendidikan Islam ideal ialah yang fleksibel serta dinamis dan bisa menyelesaikan tantangan maupun problematika yang ada sekaligus mampu mengakomodir kebutuhan-kebutuhan manusia modern. Mempertimbangkan hal tersebut, maka perlu dirumuskan dan dikembangkan kurikulum pendidikan Islam yang ideal agar tujuan dari pendidikan Islam sendiri dapat tercapai. Metode yang digunakan dalam penelitian ini ialah literature review dari berbagai pemikiran tokoh pendidikan Islam kontemporer. Hasil yang diperoleh ialah, pembaruan dalam pendidikan Islam tentunya masalah kurikulum yakni dengan peningkatan kualitas keimanan dan ketaqwaan kepada Alloh Swt, pemberian basic competencies ilmu-ilmu keislaman sebagai ciri khas pendidikan Islam, penyaluran bakat, minat dan kemampuan, pengembangan sumber daya manusia dan sumber daya bangsa di tengah-tengah kehidupan dunia. Juga dengan menghilangkan paham dikotomi dalam pendidikan Islam, mengadopsi keilmuan Barat dan tetap berorientasi sepenuhnya kepada pemurnian ajaran Islam (Al-Qur’an dan Hadits). [The ideal Islamic education curriculum is flexible and dynamic and can solve both challenges and challenges existing problems at the same time able to accommodate the needs of modern humans. Considering this, it is necessary to formulate and develop an ideal Islamic education curriculum so that the goals of Islamic education it self can be achieved. The method used in this study is a literature review of various thoughts from contemporary Islamic education figures. The results obtained are reforms in Islamic education, of course, curriculum issues , namely by increasing the quality of faith and devotion to Allah Swt, providing basic competencies of Islamic sciences as a characteristic of Islamic education, distribution of talents, interests, and abilities, development of human resources and national resources amid during in worldly life. Also by eliminating the notion of dichotomy in Islamic education, adopting Western scholarship, and remaining fully oriented towards the purification of Islamic teachings ( Al -Qur'an and Hadith).]